Case Report: Submucosal gastroblastoma with a novel PTCH1::GLI2 gene fusion in a 58-year-old man - Chen, Cuimin; Lu, Junliang; Wu, Huanwen (Frontiers in Oncology, 2022)
Abstract Gastroblastoma is a rare biphasic tumor of the stomach that generally presents in young patients. MALAT1-GLI1 gene fusion was considered to be the characteristic molecular alteration of this tumor in previous reports. Herein, we described a 58-year-old man with a mass mainly located in the submucosa of the stomach. Microscopic examination showed a biphasic morphology with the same immunohistochemical phenotype as gastroblastoma. Interestingly, a novel PTCH1::GLI2 fusion rather than MALAT1-GLI1 fusion was detected in the tumor by RNA-based next generation sequencing (NGS). This was the first report that demonstrated a novel PTCH1::GLI2 gene fusion in gastroblastoma, and thus expanded the molecular spectrum of this tumor. The underlying pathogenesis merits further investigation.